2005
DOI: 10.1161/01.atv.0000172659.01157.c6
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Infection and Selection of Culture-Derived Platelets Allows Study of the Effect of Transgenes on Platelet Physiology Ex Vivo and on Thrombus Formation In Vivo

Abstract: Background-We recently reported the development of culture-derived (CD) platelets with the aim to express any protein of interest in these platelets. 1 We now report a specific protocol of retroviral infection into the progenitor cells and subsequent selection, which allows to generate large amounts of highly homogenous transgene-expressing CD platelets and to study transgene function rapidly and reliably at large-scale ex vivo and in vivo settings. Methods and Results-After retroviral infection and selection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…5,[11][12][13][14][15] Such produced platelets are functional, as demonstrated in aggregation assays and by expression of P-selectin on the platelet surface or by activation of glycosylphosphatidylinositol (GPI) IbIIIa upon thrombin/ thrombin receptor-activating peptide (TRAP) stimulation. 6,[11][12][13][14] The nonobese diabetic/severe combined immunodeficient (NOD/ SCID) mouse model has long been accepted as the standard tool to reproduce human hematopoiesis after hematopoietic stem cell (HSC) xenoengraftment. 16 These animals present a favorable environment for efficient human progenitor cell engraftment due to various immunologic abnormalities such as T-and B-cell deficiency, defective natural killer cells, macrophage dysfunction, and absence of circulating complement.…”
mentioning
confidence: 99%
“…5,[11][12][13][14][15] Such produced platelets are functional, as demonstrated in aggregation assays and by expression of P-selectin on the platelet surface or by activation of glycosylphosphatidylinositol (GPI) IbIIIa upon thrombin/ thrombin receptor-activating peptide (TRAP) stimulation. 6,[11][12][13][14] The nonobese diabetic/severe combined immunodeficient (NOD/ SCID) mouse model has long been accepted as the standard tool to reproduce human hematopoiesis after hematopoietic stem cell (HSC) xenoengraftment. 16 These animals present a favorable environment for efficient human progenitor cell engraftment due to various immunologic abnormalities such as T-and B-cell deficiency, defective natural killer cells, macrophage dysfunction, and absence of circulating complement.…”
mentioning
confidence: 99%
“…Notably, other investigators have transfused culture-derived platelets, with similar in vitro functional activity to that described in this study, into mice and observed culture-derived platelets participating in growing blood clots in response to injury. 30,33,51,75 …”
Section: Discussionmentioning
confidence: 99%
“…Though technically not cells, blood platelets may figure prominently in these responses. It has been shown that Ads can infect platelets in vitro, and mice intravenously injected with Ad vectors can be found to contain Ads within their platelets as well (Faraday et al, 1999;Gillitzer et al, 2005;Stone et al, 2007). The significance of Ad interactions with platelets (i.e.…”
Section: Cellular Elements Of the In Vivo Innate Immune Response To Adsmentioning
confidence: 99%